Does inspiratory muscle training (IMT) change aerobic capacity in young football players? - Tomás, Maria Teresa (2021)
Introduction and background: Inspiratory muscle training (IMT) is used in several programs of pulmonary rehabilitation with good results. However, for sports performance, results are yet scarce and in football, no studies were found. Aims and objectives: The purpose of our study was to verify if an exercise training program for inspiratory muscles with eight weeks of duration will influence inspiratory muscle strength (IMS) and cardiorespiratory capacity (VO2).